2011
DOI: 10.1007/s11524-011-9627-9
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Contexts Experienced by Young Mexican-American Women: Enhancing Our Understanding of Risk for Early Childbearing

Abstract: Young Mexican-American women are disproportionately affected by teen pregnancy and early childbearing. While many of the studies that have investigated this population's high risk for early childbearing have focused predominantly on micro-level factors, a growing body of research has demonstrated the importance of neighborhoodlevel factors in shaping risk for this outcome. In order to elucidate the role of neighborhood context with regards to early childbearing among adolescent Mexican-American women, it is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The way that a researcher understands photos and the process of photography might lead to distinct methods of analysis. While all PEI research studies employ qualitative analysis methods, such as grounded theory (Biag, 2014;Richardson & Nuru-Jeter, 2012), constant comparative method (Bhukhanwala & Allexsaht-Snider, 2012), or content analysis (Agbenyega, 2008), researchers diverge in their analytical strategy in regards to whether photos will be analyzed in addition to interview transcripts. Some researchers regard photos "primarily as elicitation tools during interviews" (Werts, et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way that a researcher understands photos and the process of photography might lead to distinct methods of analysis. While all PEI research studies employ qualitative analysis methods, such as grounded theory (Biag, 2014;Richardson & Nuru-Jeter, 2012), constant comparative method (Bhukhanwala & Allexsaht-Snider, 2012), or content analysis (Agbenyega, 2008), researchers diverge in their analytical strategy in regards to whether photos will be analyzed in addition to interview transcripts. Some researchers regard photos "primarily as elicitation tools during interviews" (Werts, et.…”
Section: Discussionmentioning
confidence: 99%
“…Photos can also illuminate the importance of seemingly ordinary settings. In a study of how teenage Mexican women perceive their neighborhoods, participants took several photos of empty streets or inanimate objects (Richardson & Nuru-Jeter, 2012). Subsequent interviews revealed that these were not ordinary settings, but sites where the women had experienced violence, discrimination, or gang activity.…”
Section: Benefits and Obstaclesmentioning
confidence: 99%
“…These sorts of collaborative endeavors can more completely unpack the ways in which local place contexts are experienced and embodied on a daily basis, as well as afford guidance in identifying the political and social processes that might be implicated in residents' embodiment experiences. Adopting participatory mixed-methods approaches (see for example, Dennis and colleagues [76] and Richardson and Nuru-Jeter [77]) can help re-contextualize place and the embodiment of place by putting people back into their bodies and allowing them-the study participants-to contribute more fully to the knowledge creation process. This in turn can more readily facilitate knowledge translation and action that is timely and responsive to the social and political realities of people's daily place contexts, thus moving place-embodiment research beyond abstract and de-placed associations whose value and utility stem primarily from generalizability, not actionability.…”
Section: Embodiment In Place-health Research: Limitations As Opportunmentioning
confidence: 99%
“…Most of the work on mobility ladders and geographies of opportunity has been done using secondary data to determine neighborhood boundaries and characteristics, but this approach has limitations (detailed elsewhere: Caughy, O’Campo, & Patterson, 2001; Kim, 2012; Kramer & Hogue, 2009), pointing to the need for innovative methods that can integrate local knowledge and subjective accounts of residential context. Explorations of neighborhoods using visual and spatial methodologies have been generative in elucidating how residents—and youth residents, in particular—experience their built and social environments (Cannuscio et al, 2009; Fleury, Keller, & Perez, 2009; Matthews, Detwiler, & Burton, 2005; Richardson & Nuru-Jeter, 2012; Teixeira, 2015), and youth-driven inquiry that emphasizes participant engagement has shown the potential for enhancing our understanding of neighborhood context by highlighting the issues and assets young residents encounter in their daily lives (Foster-Fishman, Law, Lichty, & Aoun, 2010; Santo, Ferguson, & Trippel, 2010; Wilson et al, 2007). These innovative, participatory methods are ideal for developing a more nuanced understanding of how second-generation Mexican American youth perceive, experience, and pursue mobility.…”
Section: Introductionmentioning
confidence: 99%